Red-S - conceptional overview, breaking myths around weight and performance, and practical implications for coaches - Norton, J. (Techniques Magazine, 2020)
In 2014, the International Olympic Committee (IOC) convened an expert working group to update their consensus statement on the Female Athlete Triad. That group published a new statement and coined a new term: Relative Energy Deficiancy in Sport, or RED-S (Mountjoy et al, 2014). The same group published a follow-up statement in 2018 with ecpanded and updated research (Moundjoy et al, 2018). Research suggests that inadequate energy availability (EA) leads to detrimental impacts on health and athletic performance that extend beyond bone health and reproductive functions. Additionally, while more prevalent in women, low EA (LEA) also impacts male athletes; thus RED-S was presented as a broader, more encompassing syndrome to capture these effects (Mountjoy et al, 2014). "The syndrome of RED-S refers to impaired physiological function including, but not limited to, metabolic rate, menstrual function, bone health, immunity, protein synthesis, cardiovascular health caused by relative energy deficiency" (para.4) (Mountjoy et al, 2014).